Impacts of Cittaslow philosophy on sustainable tourism development - Ince, Ecem; Iscioglu, Deniz; Ozturen, Ali (Emerald Group Publishing Ltd, 2020)
Purpose - Sustainability concept exists in the soul of the Cittaslow (slow city) philosophy. This protest movement is mainly based on the philosophy of sustainability by promoting the slowness perspective and the concept of sustainable development at the local level. The purpose of this paper is to analyze the impacts of Cittaslow (slow city) philosophy on support for sustainable tourism development in North Cyprus. In this context, this research study is concentrated on the influences of Cittaslow practices on support for sustainable tourism development with dimensions in terms of socio-cultural, economic and ecological aspects. Design/methodology/approach - This study was based on a quantitative research approach to observe the significant effects and meet the objectives. The data were collected randomly by self-administrated questionnaires from residents who are living in the slow cities (Yeni Bogazici, Mehmetcik, Lefke, Gecitkale and Tatlisu) at North Cyprus. Findings - The partial least squares approach to the structural equation model was used to analyze the data. The research results were discussed the critical issues and consequences in the management of slow cities. Originality/value - The slow city concept is a very significant movement that emphasizes the importance of local differences and sustainability. There is a lack of knowledge about the effects of Cittaslow membership and efforts on sustainable tourism development in North Cyprus. The critical factors and implications were pinpointed for enhancing sustainable tourism development in slow cities.
Keywords: Cittaslow (slow city); Sustainable tourism development; Tourism development; Sustainable city; North Cyprus; Impacts of tourism